Paper based microfluidics for rapid preconcentration of micropollutants by ion preconcentration - Perera, Adhikarige Taniya Kaushalya (Nanyang Technological University, 2020)
The contamination of water bodies heavily contributes to the water scarcity experienced globally. Hence, water is continuously monitored under various quality chapters, such as physical, chemical, or biological quality, as contaminants of water vary in a wider range. The contaminants can be organic compounds, inorganic compounds, or even pathogenic microorganisms. Some contaminants may not present at levels that are detectable by conventional monitoring techniques; this is often the case for micropollutants such as heavy metal ions, antibiotic residues, pathogens, or industrial chemicals. These contaminants pose risk to human/animal life and the environment at lower concentrations, therefore it is of great importance to monitor them continuously. Nevertheless, the presence of these contaminants in potable and recreational water in tracer amounts often requires preconcentration prior to analysis, and current methods—such as solid/liquid phase extraction, followed by mass spectrometry, liquid chromatography-mass spectrometry, and so forth, or cell culturing—are time-consuming, expensive, and complex. In this scenario, the use of electrokinetic phenomena such as ion concentration polarisation (ICP) for the preconcentration of charged particles/ions in a less complicated microfluidic system with reduced specific requirements becomes a viable option for the rapid and easy detection of these micropollutants. ICP is an ionic transport phenomenon that enables the preconcentration of low-concentrated analytes, whereas microfluidics enables the use of minimal sample amounts, thus facilitating the detection process. This study focused on developing a microfluidic paper-based analytical device (µPAD) to implement ICP and study the application of ICP on a µPAD to detect various types of micropollutants, identifying its characteristics and optimising the process. First, this thesis presents a novel, rapid, inexpensive, and convenient method for fabricating µPAD, showing its feasibility to detect low concentrations of analytes through the enhanced preconcentration of samples in a shorter time. Based on the developed method, µPAD was fabricated and studied experimentally for the preconcentration of Escherichia coli through ICP, addressing the issues encountered in conventional detection methods, such as the consumption of a significant amount of time. The research proceeded to study the performance of ICP on a µPAD in detecting heavy metal ions, where ICP is characterised for such smaller ions of heavy metals. Finally, the performance of ICP in the detection of antibiotics, complex molecules that tend to change their polarity based on media, is reported. The research studied various classes of micropollutants, providing insight into the use of ICP and its characteristics based on the type of analyte from a broader perspective.